Conciousness and Matter, A Complex Relationship: The Case of Sa¯mkhya - Arnau, Juan (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The article focuses on the relationships (logic, metaphoric and epistemic) between consciousness and matter in the sa-mkhya philosophy, one of the oldest systems of the Brahmanical tradition. After a brief introduction to the cosmology of the sa-mkhya, it discusses cosmogony and metaphysical pluralism of this current of thought using as primary sources the Sanskrit medieval commentaries on the Sa-mkhyaka-rika- by the medieval scholastic Va-caspati Mis´ra.
Keywords: Sa-mkhya; sanskrit philosophy; cosmology; consciousness; matter